Perbandingan Pembinaan Olahraga Tenis Lapangan Pada Klub Junior dan Duayu di Kabupaten Bengkulu Selatan - Purmandaru, Ahmad; Mulyana, Mulyana; Irawadi, Hendri (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to determine the comparison of table tennis coaching at junior and Duayu clubs in the South Bengkulu district. This research uses a quantitative descriptive approach with a population of athletes, coaches, administrators of Junior and Duayu Tennis Clubs, and parents of athletes in Pengcab. The sample was taken by purposive sampling, involving 16 athletes, 3 coaches, 6 administrators, and 16 parents. Data analysis was carried out using frequency distribution and percentages. The results show that Junior Tennis athletes scored 83.44% and Duayu Tennis athletes 87.63%, both in the good category. Junior Tennis Club coaches achieved 82.96%, Duayu Tennis coaches 89.33%, and Junior Tennis administrators 82.26%. Parental support for Junior Tennis athletes reached 76.35% (fair) and for Duayu Tennis 81.67% (good). In conclusion, overall, athletes, coaches, administrators, and parents in South Bengkulu Regency are in the good category Key words: coaching; comparison; tennis fields